The LITERATURE REVIEW: ETHNOSCIENCE PROJECT IN SCIENCE LEARNING - Khusniati, Miranita (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
Due to the importance of ethnoscience integration in the PjBL model, many studies have been conducted on this topic. To find out the development of research on this topic, a literature review is needed on the results of research that has been carried out. The purpose of this study is to find out the topics that are often studied in research related to ethnoscience projects in science learning, as well as the development of the research in question from 2015 to 2024. The research method used is descriptive research with a bibliometric approach. The data analyzed were 843 research articles that had been published in journals on Google Scholar data. Based on the literature review that has been carried out, it was found that many studies related to ethnoscience projects in Science Learning have been conducted since 2015 to 2024. In the early years, many studies were conducted through the reconstruction of indigenous knowledge in culture, in relation to the knowledge possessed by the community. More and more, research has begun to be conducted to seek learning through the integration of ethnoscience and PjBL to improve students' abilities, attitudes, and skills.